DOI: 10.11606/d.11.2015.tde-23062015-135642
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas agroflorestais com cacau para recuperação de áreas degradadas, em São Félix do Xingu - PA

Abstract: Cacao agroforestry systems for reclamation of degraded lands in Sao Felix do Xingu-PA In contrast to the advance of the Amazon rainforest deforestation, mainly by cattle activity, in Sao Felix do Xingu-PA municipality, several initiatives have been stimulating the reclamation of degraded lands (RDL) through the implementation of agroforestry systems with cacao (Theobroma cacao L.) (cacao-AFS). Aiming to study the cacao-AFS as a potential tool to reclaim degraded lands in this region, I based the research in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
1
0
2
Order By: Relevance
“…These active strategies are adequate for lands that have undergone intensive use, resulting in compacted soil, excessive loss of organic matter, and soil seed bank pauperization (Brancalion et al, 2016). In São Félix do Xingu, where the community with the highest deforestation rate in our study is located (the surroundings of Tapirapé-Aquiri FLONA), there are several incentives for restoring degraded areas through the implementation of agroforestry systems with cacao (Theobroma cacao) (Braga, 2015). Braga (2015) interviewed 16 family farmers in this region and reported that half of them received training to work with these agroforestry systems, and 81% received seedlings from a government agency.…”
Section: Effects Of Environmental Threats On Forest Traditional Ecolo...mentioning
confidence: 97%
“…These active strategies are adequate for lands that have undergone intensive use, resulting in compacted soil, excessive loss of organic matter, and soil seed bank pauperization (Brancalion et al, 2016). In São Félix do Xingu, where the community with the highest deforestation rate in our study is located (the surroundings of Tapirapé-Aquiri FLONA), there are several incentives for restoring degraded areas through the implementation of agroforestry systems with cacao (Theobroma cacao) (Braga, 2015). Braga (2015) interviewed 16 family farmers in this region and reported that half of them received training to work with these agroforestry systems, and 81% received seedlings from a government agency.…”
Section: Effects Of Environmental Threats On Forest Traditional Ecolo...mentioning
confidence: 97%
“…The previous sections highlighted the importance and role of EPZs in promoting foreign trade, foreign direct investment, and employment around the globe. In The Asian export miracle was largely fueled by the massive creation of EPZs throughout Asia (Braga, 2019;Gouvea, 2012Gouvea, , 2014Gouvea, , 2020. (Braga, 2020b;Gaeta, 2022).…”
Section: Brazil's Foreign Trade Policies and Epzsmentioning
confidence: 99%
“…Mercosur had a positive impact on Brazil's trade with Argentina but did not inserted Brazil into the global value-added and supply chains that NAFTA would have promoted. Instead of pursuing bilateral agreements with the likes of U.S. and the EU, and even pursuing membership in other regional economic agreements, Brazil made a clear decision to avoid exposing its heavily protected industry from competition (Braga, 2019;Braga, 2020a;Gouvea, Gutierrez, Montoya, & Terra, 2021;Noronha, 2022).…”
Section: Brazil's Foreign Trade Policies and Epzsmentioning
confidence: 99%
“…De acordo com a percepção dos produtores sobre sua renda, anualmente a pecuária rende em média R$ 394,37 por hectare, e a produção de cacau rende anualmente R$ 3.257,75 por hectare, aproximadamente 8 vezes mais. Estes dados também são similares aos encontrados por Braga (2015), que realizou sua pesquisa no mesmo município e concluiu que após o sexto ano de cultivo do cacau, a renda pode ser de 4 a 6 vezes maior do que o valor da pecuária.…”
Section: Caracterização Dos Produtores E Do Manejo Agroflorestalunclassified
“…Considerando as médias de produtividade para SAFs-cacau produtivos obtidas por Braga (2015) para a mesma região, de 471,4 kg de amêndoas secas/ha/ano, e a média de produtividade de 354,32 kg/ha/ano estimada neste trabalho, obtemos uma média local de 412,86 kg de amêndoas de cacau por hectare/ano.…”
Section: Regressão Carbono Acima Do Solo De áRvores De Sombreamento X Icdunclassified